LEGAL PROTECTION FOR DONATORS AGAINST ACTIONS BY DONATION RECIPIENTS WHO MISAPPROPRIATE DONATION MONEY - Gani, Junaidi Syahputra; Handayani, Pristika; Abra, Emy Hajar (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
In reality, collecting donations often does not match the original purpose of providing the funds. This is a common occurrence and is frequently reported by television, mass media, and online media. In this study, several issues are examined, including the implementation of regulations regarding donations, the legal protection afforded to donors against the misuse of donation funds by recipients, and the solutions for actions taken by recipients who misuse donation funds. The form of this research is normative legal research, utilizing secondary data as its primary source of information. The data analysis used is qualitative descriptive analysis. Legal protection for donors in the context of acts of misuse of donation money by recipients of donations is a complex issue and requires serious attention. On the one hand, existing regulations have provided a sufficient legal framework to protect donors; on the other hand, there are still many challenges to their implementation in the field. Cases of misuse that occur show that the existing regulations are not fully effective in preventing misuse of funds. It is essential to strengthen the supervision and accountability of institutions that collect donations. Transparency in fund management, independent audits, and certification for trusted foundations are some steps that can be taken to increase donor trust. In addition, educating the public about their rights as donors is also crucial in building better legal awareness. With the various solutions proposed, the donation ecosystem in Indonesia can become more efficient and transparent. The public must feel safe and confident that every donation given will be used for the right purpose. Only in this way can we build a healthy and sustainable donation culture in Indonesia.